Cross-Lagged Analysis of COVID-19-Related Worry and Media Consumption in a Socioeconomically Disadvantaged Sample of Community Adults - Bounoua, Nadia; Goodling, Shelly; Sadeh, Naomi (Frontiers in Psychology, 2021)
The COVID-19 pandemic has led to an increase in an array of mental health problems. Previous research has shown that media exposure to stressful situations is often related to anxiety and stress. However, given that most existing work has used cross-sectional designs, less is known about the interplay of media exposure and worry as they unfold during sustained exposure to a collective stressor. The current study examined bidirectional associations between COVID-related worry and media consumption over a three-month period. Participants were 87 community adults, the majority of whom were recruited from communities heavily impacted by the COVID-19 pandemic. For three consecutive months, participants asked to indicate how much time they spent worrying and consuming news about the COVID-19 pandemic on a scale from 1 (“never”) to 5 (“most of the day”). Cross-lagged analyses revealed that Pandemic Worry at Month 1 predicted increases in Pandemic Media Consumption at Month 2, which in turn predicted increases in Pandemic Worry at Month 3. Findings suggest that media consumption may be a maladaptive coping strategy that has the iatrogenic effect of increasing worry. Clarifying the causal associations between anxiety-perpetuating processes and media consumption may have important clinical implications for understanding and treating mental health during health pandemics.